Best practice kebijakan e-government dalam mengimplementasikan pelayanan publik di era new normal - Tasyah, Amelia; Septiya, Septiya; Putri, Sabrina Jasriyani; Fernanda, Reza Agung; Azani, Putri Chesilia (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: This research aimed to examine the extent to which the best practice of public service policies utilizing e-government and how much e-government policies need to be enforced in the new normal era. Research methodology: This research used a purposive sampling method. This research is qualitative data where the required data are statements and policies related to community participation in Bandar Lampung city. Results: The results show that many people do not understand e-government policy and its implementation is not optimal. Limitations: This study has limitations in accessing the number of respondents in taking research samples with qualitative techniques through questionnaires and their relationship to document studies. Contribution: This research is expected to be useful in improving public services amid a pandemic and being a consideration for the government in practicing an effective and efficient e-government policy as a form of implementing Best Practice, especially in regions of Indonesia.